Pravastatin-induced improvement in coronary reactivity and circulating ATP and ADP levels in young adults with type 1 diabetes - Kiviniemi, Tuomas O.; Yegutkin, Gennady G.; Toikka, Jyri; Paul, Subhadeep; Aittokallio, Tero; Janatuinen, Tuula; Knuuti, Juhani; Rönnemaa, Tapani; Koskenvuo, Juha; Hartiala, Jaakko; Jalkanen, Sirpa; Raitakari, Olli T. (Frontiers in Physiology, 2012)
Aims: Extracellular ATP and ADP regulate diverse inflammatory, prothrombotic and vasoactive responses in the vasculature. Statins have been shown to modulate their signaling pathways in vitro. We hypothesized that altered intravascular nucleotide turnover modulates vasodilation in patients with type 1 diabetes (T1DM), and this can be partly restored with pravastatin therapy. Methods: In this randomized double blind study, plasma ATP and ADP levels and echocardiography-derived coronary flow velocity response to cold pressor test (CPT) were concurrently assessed in 42 normocholesterolemic patients with T1DM (age 30±6 years, LDL cholesterol 2.5±0.6 mmol/L) before and after four-month treatment with pravastatin 40 mg/day or placebo (n=22 and n=20, respectively), and in 41 healthy control subjects. Results: Compared to controls, T1DM patients had significantly higher concentrations of ATP (p<0.01) and ADP (p<0.01) and these levels were partly restored after treatment with pravastatin (p=0.002 and p=0.007, respectively), but not after placebo (p=0.06 and p=0.14, respectively). Coronary flow velocity acceleration was significantly lower in T1DM patients compared to control subjects, and it increased from pre- to post-intervention in the pravastatin (p=0.02), but not in placebo group (p=0.15). Conclusions: Pravastatin treatment significantly reduces circulating ATP and ADP levels of T1DM patients, and concurrently improves coronary flow response to CPT. This study provides a novel insight in purinergic mechanisms involved in pleiotropic effects of pravastatin.